Chronic sensory stroke with and without central pain is associated with bilaterally distributed sensory abnormalities as detected by quantitative sensory testing. Issue 1 (January 2016) - Krause, Thomas; Asseyer, Susanna; Geisler, Frederik; Fiebach, Jochen B.; Oeltjenbruns, Jochen; Kopf, Andreas; Villringer, Kersten; Villringer, Arno; Jungehulsing, Gerhard J.
Abstract : Abstract: Approximately 20% of patients suffering from stroke with pure or predominant sensory symptoms (referred to as sensory stroke patients) develop central poststroke pain (CPSP). It is largely unknown what distinguishes these patients from those who remain pain free. Using quantitative sensory testing (QST), we analyzed the somatosensory profiles of 50 patients with chronic sensory stroke, of which 25 suffered from CPSP. As compared with reference data from healthy controls, patients with CPSP showed alterations of thermal and mechanical thresholds on the body area contralateral to their stroke ( P < 0.01). Patients with sensory stroke but without CPSP (non–pain sensory stroke [NPSS] patients) exhibited similar albeit less pronounced contralesional changes. Paradoxical heat sensation (PHS) and dynamic mechanical allodynia (DMA) showed higher values in CPSP, and an elevated cold detection threshold (CDT) was seen more often in CPSP than in patients with NPSS ( P < 0.05). In patients with CPSP, changes in CDT, PHS, dynamic mechanical allodynia, and temporal pain summation (wind-up ratio) each correlated with the presence of pain ( P < 0.05). On the homologous ipsilesional body area, both patient groups showed additional significant abnormalities as compared with the reference data, which strongly resembled the contralesional changes. In summary, our analysis reveals that CPSP is associated with impaired temperature perception and positive sensory signs, but differences between patients with CPSP and NPSS are subtle. Both patients with CPSP and NPSS show considerable QST changes on the ipsilesional body side. These results are in part paralleled by recent findings of bilaterally spread cortical atrophy in CPSP and might reflect chronic maladaptive cortical plasticity, particularly in patients with CPSP. Abstract : Chronic stroke patients with and without central pain show considerable abnormalities on the ipsilesional body side, whereas sensory differences between patient groups are subtle.Supplemental Digital Content is Available in the Text.